TINJAUAN AKULTURASI BUDAYA PADA FACADE (EXTERIOR) MASJID AL-ANWAR MUARA ANGKE – JAKARTA - Alamsyah, Muhammad; Kasman (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
Jakarta has many old mosques that have historical values. The existence of themosques began since the establishment of Jakarta, after the conquest of Sunda Kelapaby the joint forces of Demak-Cirebon led by Falatehan in 1527, until Indonesia'sIndependence in 1945. Within four centuries, in Jakarta, mushallas and mosques havegrown and developed to fulfill spiritual and the needs of the struggle of Muslims in theface of Dutch colonialism. Many ethnic groups contributed to the building andprosperity of the mosque. One of the famous old mosques in Jakarta is the Jami AngkeMosque in Muara Angke. This study aims to explore the mixture of architectural forms,which in this study is called architectural acculturation, in the architecture of the Al-Anwar Muara Angke Mosque Facade which is allegedly brought by ethnic or ethnicgroups to Jakarta, both ethnic groups from outside such as Chinese, Arabic and Dutch.itself, as well as ethnic groups themselves, such as Java, Bali, and so on. Theacculturation process is determined based on the dominance of one architectural form.There are four possible processes for architectural acculturation, namely adaptation,adoption, synergy, and marginalization